1992
DOI: 10.1037/0022-3514.63.5.781
|View full text |Cite
|
Sign up to set email alerts
|

Threat, cohesion, and group effectiveness: Testing a social identity maintenance perspective on groupthink.

Abstract: Although Janis's concept of groupthink is influential, experimental investigations have provided only weak support for the theory. Experiment 1 produced the poor decision quality associated with groupthink by manipulating group cohesion (using group labels) and threat to group members' self-esteem. Self-reports of some groupthink and defective decision-making symptoms were independently, but not interactively, affected by cohesion and threat. Experiment 2 confirmed the success of the cohesion manipulation. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 53 publications
6
103
0
3
Order By: Relevance
“…At the group level, similarity also fosters group cohesion (e.g. Callaway & Esser, 1984;Callaway, Marriott & Esser, 1985;Turner, Pratkanis, Probasco, & Leve, 1992), and similarity "at work"-the congruence between people and their work environment-is associated with various positive organizational outcomes (for overviews, see Edwards et al, 2006;Hoffman & Woehr, 2006;Kristof-Brown et al, 2005). While similarity has important consequences for a wide range of outcomes, its role in leadership effectiveness has received relatively limited attention.…”
Section: Similaritymentioning
confidence: 99%
“…At the group level, similarity also fosters group cohesion (e.g. Callaway & Esser, 1984;Callaway, Marriott & Esser, 1985;Turner, Pratkanis, Probasco, & Leve, 1992), and similarity "at work"-the congruence between people and their work environment-is associated with various positive organizational outcomes (for overviews, see Edwards et al, 2006;Hoffman & Woehr, 2006;Kristof-Brown et al, 2005). While similarity has important consequences for a wide range of outcomes, its role in leadership effectiveness has received relatively limited attention.…”
Section: Similaritymentioning
confidence: 99%
“…Specifically, the factors that contributed to this irrational behavior include direct pressure on dissenters (group members are under social pressure to not oppose the group consensus), self-censorship (doubts and deviations from the perceived group consensus are not accepted) and the illusion of unanimity. Turner et al [20,21] also showed that groupthink is most likely to occur when a group experiences antecedent conditions, such as high cohesion, insulation from experts and limited methodological search and appraisal procedures, and leads to symptoms, such as the illusion of invulnerability, the belief in the inherent morality of the group, pressure on dissenters, self-censorship and the illusion of unanimity. More concretely, the symptoms of groupthink, i.e., (1) incomplete analysis of the alternatives, (2) incomplete analysis of the objectives and (3) failure to examine the risks of the preferred choice, were observed during the occurrence of the Challenger space shuttle disaster.…”
Section: Challenger Space Shuttle Disastermentioning
confidence: 99%
“…Rather than basing leadership on leader schemas that generally contain optimal situation and task-specific leadership prescriptions, a situation can exist where there is a powerful leader who embodies a group prototype that does not prescribe optimal decision-making procedures. This may produce groupthink (Janis, 1972); powerful leaders and the absence of norms for optimal decision making conspire in highly cohesive groups to produce suboptimal decision-making procedures that lead to poor decisions M. E. Turner, Pratkanis, Probasco, & Leve, 1992).…”
Section: Pitfalls Of Prototype-based Leadershipmentioning
confidence: 99%